LOGOPEDIC AND PEDAGOGICAL MECHANISMS OF DEVELOPING DIALOGIC SPEECH IN PRESCHOOL CHILDREN IN THE DIGITAL EDUCATIONAL ENVIRONMENT - Yalgasheva Zilola (International Scientific and Current Research Conferences, 2025)
This article substantiates an integrated system of logopedic and pedagogical mechanisms for developing dialogic speech in preschool children within a digital educational environment. Building on socio-cultural and interactionist theories, we argue that digital tools can amplify adult–child and peer–peer dialogue when they are embedded in logopedic micro-techniques and coherent pedagogical design. The paper clarifies how articulation placement, phonemic cueing, rhythmic pacing, and semantic–pragmatic scaffolding can be operationalized through multimedia feedback, adaptive tasks, and dialogic storytelling applications. A practice-oriented model is proposed that aligns therapist–teacher co-planning, multimodal prompts, scripted micro-dialogues, and parent tele-coaching. We describe a feasible twelve-week implementation framework and an evaluation strategy combining conversational analysis, turn-taking metrics, and standardized language measures. The article concludes with practical recommendations on combining digital resources with evidence-based logopedic techniques and dialogic pedagogy while safeguarding children’s well-being and equity of access.